Towards a IoT secure smart environment system - Oliveira, Pedro Filipe (2020)
Currently IoT systems are in a big security risk. Especially because the developers, are not worried enough about the safety of such systems. However, with the growing trend of such systems and is integration in our everyday lives, this concern will have to increase as they start to appear isolated cases which have harmed the users, both financially and in their safety and welfare. The proposed security architecture, to one of these IoT systems, wants to avoid any of the presented risks, to the users of this system. For future work, we have identified the need to develop solutions that enable communication between the application and the local system, using different communication technologies without user interaction. Some extra work must be done to overcome this constraint, and get a transparent use solution for every user.